2017
DOI: 10.1002/tox.22397
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silver nanoparticles on the interactions of neuron‐ and glia‐like cells: Toxicity, uptake mechanisms, and lysosomal tracking

Abstract: Silver nanoparticles (AgNPs) are commonly used nanomaterials in consumer products. Previous studies focused on its effects on neurons; however, little is known about their effects and uptake mechanisms on glial cells under normal or activated states. Here, ALT astrocyte-like, BV-2 microglia and differentiated N2a neuroblastoma cells were directly or indirectly exposed to 10 nm AgNPs using mono- and co-culture system. A lipopolysaccharide (LPS) was pretreated to activate glial cells before AgNP treatment for mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 63 publications
(125 reference statements)
3
31
0
1
Order By: Relevance
“…An analogous research of the absorption of Ag NPs showed less uptake by neuroblastoma N2a cells, as compared to ALT and BV-2 cells. In ALT cells prevailed phagocytosis and clathrin/caveolae independent endocytosis, while in BV-2 Ag NPs were taken mainly by micropinocytosis and clathrin-mediated endocytosis [75].…”
Section: Cellular Uptakementioning
confidence: 98%
“…An analogous research of the absorption of Ag NPs showed less uptake by neuroblastoma N2a cells, as compared to ALT and BV-2 cells. In ALT cells prevailed phagocytosis and clathrin/caveolae independent endocytosis, while in BV-2 Ag NPs were taken mainly by micropinocytosis and clathrin-mediated endocytosis [75].…”
Section: Cellular Uptakementioning
confidence: 98%
“…The printing parameters were as in table 5 for PAN+CNT samples (Ø nozzle =610 μm, s=50 mm min −1 , z=1.5 mm, p=1.25 bar). Specifically, three samples were printed at n=40 layers and three at n=1 layer to highlight the effect of the quantity of printed silver (Ø avg,particle size ∼100 nm) on cell viability, as mentioned in the literature [51,[54][55][56][57][58][59][60][61]. The samples were subjected to the same post-sintering process as for SI-AJ20X ink (180°for 1 h in a Heraeus oven), although a different ink-substrate wettability has to be considered.…”
Section: Cell Viability Assay On Hfs Up To 48 Hmentioning
confidence: 99%
“…Specifically, in biological solutions, the AgNP surface can be mainly oxidized by O 2 , activating the release of Ag + ions, which can interact with nucleic acids, lipid molecules and proteins, causing oxidative stress and damaging several cellular components [53]. On the other hand, to the best of our knowledge, most of the studies on in vitro cell cultures, report cytotoxicity of AgNP powders at various concentrations [51,[54][55][56][57][58][59][60][61], with a Ø avg particle size ≪ 100 nm, i.e. much smaller than the AgNP ink suspension used in our study (Ø avg,particle size ∼100 nm).…”
Section: Introductionmentioning
confidence: 99%
“…The BODIPY FL C5-LacCer complexed to BSA (LacCer, Molecular Probes, Eugene, OR, USA) uptake assay was modified from that previously described. [41][42][43] Briefly, cells were plated on coverslips and washed with HEPESbuffered minimal essential medium (HMEM+G) containing (in mM) 13.8 Hepes, 137 NaCl, 5.4 KCl, 2.0 glutamine, 0.4 KH 2 PO 4 , 0.18 Na 2 HPO 4 , 5.5 glucose, pH 7.4. Syt11-KO, or rescue astrocytes were then incubated with HMEM+G containing 100 nM LacCer for 30 minutes at 10°C.…”
Section: Lactosylceramide (Laccer) Uptakementioning
confidence: 99%
“…The knockout efficiency reached 83.77% ± 6.52% at the protein level, while Cav1 and EHD2 remained largely unaffected and cavin1 was slightly downregulated ( Figure 1C). LacCer, a sphingolipid analog often used to indicate caveolae-mediated endocytosis, [41][42][43] was internalized in a time-dependent manner both in control and Syt11-KO astrocytes ( Figure 1D), while its uptake was markedly enhanced in KO cells. It was accelerated by ~1.5 times compared to control except at the 5-min time point (1.2-fold).…”
Section: Syt11 Inhibits Caveolae-mediated Endocytosis In Astrocytesmentioning
confidence: 99%